Replenishment subscription services : the impact of product satisfaction, awareness, and perception on consumers’ intention to subscribe - Stahuber, Franziska Katharina (2020)
For the last five years, subscription e-commerce has grown by over 100% p.a. in the US – presenting a fast-growing channel of purchasing online. FMCG companies can increase revenue streams by offering products through a Replenishment Subscription Service (RSS). RSS offers grocery and commodity products via automated, periodic deliveries which save consumers time and effort. Quantitative research surrounding RSS has remained scarce which results in identifying two research needs: Understand consumers’ decision process to subscribe to RSS by lending a framework for innovation adoption, which includes the revised stages of awareness, perception, and intention to subscribe. Analyze product requirements since it is questioned if consumers, who are satisfied with their current product choice, are more likely to subscribe and hence, repurchase their products through RSS? Therefore, the study equates a standard repurchase process triggered by satisfaction with the periodic purchase through RSS. The goal was to study the impact of product satisfaction, awareness, and perception about RSS on consumers’ intention to subscribe. Consumers’ level of product satisfaction about RSS significantly impacts the intention to subscribe. Perception about advantages, ease of use and, compatibility with shopping habits were positive indicators for subscribing. Consumers’ overall perception fully mediates the relationship of awareness and partially mediates the relationship of product satisfaction on the intention to subscribe to RSS. Building on findings, the paper gives implications and recommendations for companies to market RSS with its products and, to target consumers in an appropriate way to increase subscription rates.